Lope de Vega Carpio, Comedias, Parte XVII, eds. Daniele Crivellari; Eugenio Maggi - Francesca Leonetti (Cuadernos AISPI, 2019)
Lope de Vega Carpio, Comedias, Parte XVII, eds. Daniele Crivellari; Eugenio Maggi